Nalbuphine in Pediatric Emergence Agitation Following Cochlear Implantation: A Randomized Trial - Li Y; Li Q; Zhao G; Zhang H; Zhong H; Zeng Y (Dove Medical Press, 2024)
Yan Li, Qi Li, Guangchao Zhao, Haopeng Zhang, Haixing Zhong, Yi Zeng Department of Anesthesia and Perioperative Medicine, Xijing Hospital, the Fourth Military Medical University, Xi'an, 710000, People's Republic of ChinaCorrespondence: Yi Zeng; Haixing Zhong, Department of Anesthesia and Perioperative Medicine, Xijing Hospital, the Fourth Military Medical University, Xi'an, 710000, People's Republic of China, Tel +8613991267646 ; +8613991946615, Email zengyi1014@163.com; haixing.zhong@139.comBackground: To investigate the effects of nalbuphine on emergency agitation (EA), which affects up to 80% of the children following otolaryngology procedures, in children undergoing cochlear implantation.Methods: A prospective double-blinded randomized controlled clinical trial was conducted between November 2020 and October 2022. Eligible children, aged 6 months to 3 years old, were randomly assigned to either 0.1 mg/kg, 0.15 mg/kg, 0.2 mg/kg nalbuphine or 0.9% saline groups. EA was defined by the Pediatric Anesthesia Emergence Delirium (PAED) score ≥ 10. Extubation time, post-anesthesia care unit (PACU) length of stay, severe EA (PAED ≥ 15), peak PAED score, the Faces, Legs, Activity, Cry, and Consolability (FLACC) scale, Ramsay sedation score, and adverse events were also recorded.Results: A total of 104 children were enrolled, with 26 children in each group. Nalbuphine significantly reduced the EA occurrence from 73.1% in the saline group to 38.5%, 30.8%, and 26.9% in the 0.1 mg/kg, 0.15 mg/kg, and 0.2 mg/kg nalbuphine groups, respectively (P < 0.001), without affecting the extubation time and PACU length of stay. More children (34.6%) in the 0.9% saline group experienced severe EA. Higher dose nalbuphine (0.15 mg/kg, 0.2 mg/kg) showed lower peak PAED score, better analgesia and sedation effect compared with 0.1 mg/kg nalbuphine and saline groups. However, 0.2mg/kg nalbuphine caused undesired over-sedation in two (7.7%) children. No other adverse events were reported.Conclusion: Young children undergoing cochlear implantation surgery were at a high risk of EA and postoperative pain, while 0.2 mg/kg nalbuphine might be an ideal candidate for EA and pain prevention when used under close monitoring.Trial Registration: ChiCTR2000040407.Keywords: emergence agitation, nalbuphine, cochlear implantation, postoperative pain